Modeling Research Competency of Faculty Member : A Preliminary Data (Sains Humanika, 2021)
Research productivity of higher education institutions (HEIs) in Indonesia lags behind those in other countries in the region, that implicates their reputation. Because in aggregation, research productivity of HEI  is the productivity of its faculty members, thus research competency of faculty members might be the factors that cause the low research productivity of those HEIs in Indonesia. Focusing on Faculty economics and Business, this paper aims to develop the model of research competency for faculty member. This paper show the analytical process used by author in modeling research competency using behavioral event interview (BEI).  The preliminary data used in this paper consist of two subjects, the effective and outstanding performer, out of minimum seven respondents that have been targeted. The findings reveal that outstanding performer tend to show more people-focused behavior than task-focused behavior.  It is consistent with the previous studies of competency modeling for professional / knowledge workers.
Keywords: Research competency; competency model; behavioral event interview (BEI)